2020
DOI: 10.1007/s00153-020-00722-x
|View full text |Cite
|
Sign up to set email alerts
|

Classifying material implications over minimal logic

Abstract: The so-called paradoxes of material implication have motivated the development of many nonclassical logics over the years [2][3][4][5]11]. In this note, we investigate some of these paradoxes and classify them, over minimal logic. We provide proofs of equivalence and semantic models separating the paradoxes where appropriate. A number of equivalent groups arise, all of which collapse with unrestricted use of double negation elimination. Interestingly, the principle ex falso quodlibet, and several weaker princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, such an embedding is not possible if the domain contains a single element. It was shown above that DP holds in models with branches if the domain contains only one term, while in [6] it is shown that DGP holds only in v-free models. Therefore there can be no way of deriving instances of DGP from DP without an embedding using two or more elements in the domain.…”
Section: Separations Without Full Modelsmentioning
confidence: 95%
See 4 more Smart Citations

The Drinker Paradox and its Dual

Warren,
Diener,
McKubre-Jordens
2018
Preprint
Self Cite
“…However, such an embedding is not possible if the domain contains a single element. It was shown above that DP holds in models with branches if the domain contains only one term, while in [6] it is shown that DGP holds only in v-free models. Therefore there can be no way of deriving instances of DGP from DP without an embedding using two or more elements in the domain.…”
Section: Separations Without Full Modelsmentioning
confidence: 95%
“…A n hold for every formula. A full model, as described in [6], is sufficient. A full model is one where we can freely create predicates, as long as they satisfy the usual monotonicity requirements.…”
Section: Technical Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations

The Drinker Paradox and its Dual

Warren,
Diener,
McKubre-Jordens
2018
Preprint
Self Cite